TWO-DIMENSIONAL SIMULATIONS VIA FINITE ELEMENTS OF DIRECT ETHANOL FUEL CELLS (DEFC) - Souza, Marcelo Maraschin de; Gomes, Ranon de Souza; De Bortoli, Alvaro Luiz (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
A solution to the growing energy demand and depletion of oil supplies is its best use,along with the development of renewable sources according to the needs and possibilities of each user. An attractive alternative is the fuel cell. Fuel cells provide clean energy and with high efficiency in a wide variety of applications. In addition, they enable greater reliability in power supply with less emissions of pollutants in the air. The present work develops a two-dimensional model for a direct ethanol fuel cell. A code is developed in Fortran90 using the finite element method to calculate the flow in different layers of the cell (input and output channels, diffusion layer and catalyst layer). The model takes into account the losses overpotentials at the anode and at the cathode, providing a better understanding of the physical and chemical behavior within the cell, and about the conversion of chemical energy into electricity. This corresponds to the main contribution of the present work.